Acute cardiac decompensation in a patient with beta‐thalassemia and diabetes mellitus following cessation of chelation therapy. Issue 10 (12th September 2016) - Lioudaki, Eirini; Whyte, Martin
Key Clinical Message: Patients with higher liver iron stores are likely to have a worse cardiac outcome following noncompliance with chelation. Cardiovascular magnetic resonance identifies myocardial siderosis allowing optimization of iron chelation regimes. Diabetes puts thalassemic patients at increased risk of myocardial fibrosis. Dual chelation therapy with deferoxamine and deferiprone offers improved cardiac outcomes. Abstract : Patients with higher liver iron stores are likely to have a worse cardiac outcome following noncompliance with chelation. Cardiovascular magnetic resonance identifies myocardial siderosis allowing optimization of iron chelation regimes. Diabetes puts thalassemic patients at increased risk of myocardial fibrosis. Dual chelation therapy with deferoxamine and deferiprone offers improved cardiac outcomes.